A History of Gap Junction Structure: Hexagonal Arrays to Atomic Resolution. (February 2013) - Grosely, Rosslyn; Sorgen, Paul L.
Abstract Gap junctions are specialized membrane structures that provide an intercellular pathway for the propagation and/or amplification of signaling cascades responsible for impulse propagation, cell growth, and development. Prior to the identification of the proteins that comprise gap junctions, elucidation of channel structure began with initial observations of a hexagonal nexus connecting apposed cellular membranes. Concomitant with technological advancements spanning over 50 years, atomic resolution structures are now available detailing channel architecture and the cytoplasmic domains that have helped to define mechanisms governing the regulation of gap junctions. Highlighted in this review are the seminal structural studies that have led to our current understanding of gap junction biology.